Eigen Beam Based Sound Source Localization Algorithms Evaluation on a Non-Spherical Microphone Array - Shan Gao; Liu, Rui; Xihong Wu; Tianshu Qu (2019 IEEE 2nd International Conference on Information Communication and Signal Processing (ICICSP), 2019)
The traditional eigen beam based localization algorithms are usually not employed on the non-spherical microphone array, for which the eigen beam is hard to be obtained. In this paper, the transfer functions are introduced to calculated the eigen beam on the non-spherical microphone array. Based on it, three localization algorithms including the eigen beam based intensity vector, eigen beam based beamforming, eigen beam based MUSIC, are employed and their performance on localization are evaluated.